Topical antibiotics with steroids for chronic suppurative otitis media - Brennan-Jones, C; Chong, L; Head, K; Tu, N; Burton, M; Schilder, A; Bhutta, M (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of adding a topical steroid to topical antibiotics in the treatment of people with chronic suppurative otitis media (CSOM).